Effectiveness of Online Zakat during the Covid-19 Pandemic by Amil Zakat Institutions in Boyolali, Indonesia - Lukmanul Hakim; Anggara Indra Setyaningsih (Department of Islamic Economics, Islamic University of Indonesia, 2022)
Zakat is the third pillar of Islam that should be fulfilled for Muslims and has a high worship value in Allah SWT. The existence of this zakat can alleviate poverty and increase state income if a country can optimize the collection of zakat funds. One way to optimize the collection is to use digital technology. At this time, the amil zakat institution has harnessed the complexity of digital technology to collect zakat funds online. This study aims to determine the effectiveness of online zakat and which amil zakat institution is more efficient in using online zakat, specifically at the amil zakat institutions: BAZNAS Boyolali, LAZISMU Boyolali, and LAZ Harapan Umat Boyolali. The research used is a type of qualitative research. The data is derived from primary sources such as interviews and documentation and secondary sources such as scientific articles. The results of this study show that online zakat is quite effective to use, as evidenced by the percentage increase in funds from 2019-2021. BAZNAS Boyolali increased by 15.9%, LAZISMU Boyolali increased by 118%, and LAZ Harapan Umat Boyolali increased by 91%. Additionally, it can be demonstrated by the fewest flaws and complaints about Online zakat. It can provide convenience for muzakki to pay zakat wherever and whenever. The most popular online zakat payment option is WhatsApp for individuals and payroll for ASN or other private employees.